ntesis Perekat Kayu Lignin–Urea Formaldehida (LUF) Berbasis Lignin yang Diekstraksi dari Tandan Kosong Kelapa Sawit (TKKS - Dian Wardana; Eddiyanto; Nurfajriani; Dwi Sapri Ramadhan; Wulan Dwi Safitri; Jam'an Fahmi (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2026)
Oil palm empty fruit bunches are one of the underutilized plantation wastes. Lignin is one of the components of plant cell walls besides cellulose and hemicellulose that can be used as a raw material for the synthesis of lignin-based adhesives, namely lignin-urea-formaldehyde (LUF) adhesive resins. The polymerization reaction of LUF formation was confirmed from the shift and change in the FTIR wavenumber of the -CO-ether group of LUF compared to UF and LF obtained during the synthesis process. The tensile strength test results of all adhesives produced exceeded the tensile strength value of commercial UF adhesives, and it was found that increasing the lignin concentration in the synthesized adhesives was directly proportional to the tensile strength value. Increasing the lignin concentration was also able to reduce formaldehyde emissions from all variations of adhesives produced, but was unable to exceed the lower formaldehyde emission value of UF adhesives.